Comparison of fetal bovine serum and platelet-rich plasma on human lipoaspirate-derived mesenchymal stem cell proliferation (Medical Journal of Indonesia, 2013)
Background: Lipoaspirate-derived stem cells (LSCs) are very promising for regenerative medicine, e.g. to treat acute myocard infarction. Fetal bovine serum (FBS) is commonly used to propagate the LSCs. However, for its clinical application, FBS contains xeno-proteins that are potential to elicit immune rejection in patients. Platelet rich plasma (PRP) is one of the candidates to replace FBS. This study was aimed to compare the proliferation of LSCs cultured in 5% PRP, 10% PRP, and FBS containing medium (MesenCult®). Methods: LSCs were cultured in 5% PRP/DMEM, 10% PRP/DMEM, and MesenCult®. After the primary culture reached its confluency, cells were harvested using TrypLE Select and seeded (around 20,000 viable cells) in new vessels in the same media. Passages were done until passage-5, with six replications. Population doubling time (PDT) of the three groups were analyzed using Kruskal Wallis test. Results: LSCs showed different proliferation rates when cultured in 5% PRP/DMEM, 10% PRP/DMEM, and MesenCult®. PDT of the three experimental groups in passage 1-5 were significanly different (p < 0.05), with the lowest rank was cultured in medium of 10% PRP/DMEM. Conclusion: The results suggest that 10% PRP/DMEM can be used as an alternative to replace FBS in LSC culture.